Assessing Short-term Deterioration in Maintenance-naïve Patients with COPD Receiving Umeclidinium/Vilanterol and Tiotropium: A Pooled Analysis of Three Randomized Trials. Issue 12 (January 2017) - Maleki-Yazdi, M.; Singh, Dave; Anzueto, Antonio; Tombs, Lee; Fahy, William; Naya, Ian
Abstract Introduction Dual bronchodilator therapy is reserved as a second-line treatment in patients with chronic obstructive pulmonary disease (COPD) and provides benefits in lung function and health status versus monotherapy. The aim of this study was to determine whether early initiation of a dual bronchodilator versus monotherapy reduced the risk of deterioration in COPD. Methods This post hoc pooled analysis investigated the efficacy and safety of umeclidinium/vilanterol (UMEC/VI) 62.5/25 mcg/day compared with tiotropium (TIO) 18 mcg/day in a maintenance-naïve (MN) subgroup of patients relative to the intent-to-treat (ITT) population from three 6-month active comparator studies (n  = 1747). Other treatment arms (UMEC/VI 125/25, VI 25 and UMEC 125) comprised 850 patients in total but were not included in this analysis. The primary endpoint was trough forced expiratory volume in 1 s (FEV1 ). St George's Respiratory Questionnaire (SGRQ) score, rescue medication use, and a novel composite endpoint of short-term clinically important deterioration (CID; ≥100 ml decrease in trough FEV1, ≥4-unit increase in SGRQ score, or a COPD exacerbation) were also assessed. Results UMEC/VI improved trough FEV1 versus TIO at day 169 [least squares mean (95% confidence interval): MN: 146 ml (102–189) and ITT: 95 ml (71–118); bothP  < 0.001]. Both UMEC/VI and TIO improved SGRQ and rescue use in the two populations, with greater improvements in rescue use with UMEC/VI versus TIO. UMEC/VI reduced the risk of short-term clinically important deterioration versus TIO [hazard ratio; 95% confidence interval: MN: 0.66 (0.51–0.85); ITT: 0.62 (0.54–0.71), bothP  ≤ 0.001]. Adverse events were similar across both populations and treatments. Conclusions Early use of dual-bronchodilator therapy has superior efficacy on lung function and may reduce the risk of short-term deterioration compared to monotherapy in symptomatic patients with COPD. Clinical trial registration : GSK analysis 202066 (NCT01316900/DB2113360, NCT01316913/DB2113374, NCT01777334/ZEP117115). Funding : This study was funded by GSK.